Improved Self‐Powered Photoresponse of ZnO Nanorods/SnS Nanosheets/PEDOT:PSS Heterostructure by Pyro‐Phototronic Effect - Weixin Ouyang; Haoxuan Geng; Jianyuan Wang (Advanced Materials Interfaces)
Abstract A ZnO nanorods/SnS nanosheets/PEDOT:PSS (ZSP) heterostructure is constructed by vapor growing a SnS nanosheets layer and spin‐coating a PEDOT:PSS layer onto ZnO nanorods arrays. By controlling the growth time of the ZnO nanorods, a series of ZSP heterojunction samples with various ZnO layer thicknesses are prepared. The formation of heterostructures contributed to the improved pyroelectric performance and fast response speed of these as‐prepared ZSP photodetectors (PDs). The thickness of the ZnO nanorod layer plays an important role in tuning the photoelectric performance of these PDs. For the optimized ZSP PD with an 800 nm thick ZnO layer, the pyroelectric effect improves its photocurrent by 137% at 365 nm and 0 V bias, and the ratio of the pyroelectric current to the photoelectric current reaches as high as 870% at 532 nm. This device also displays an ultra‐short rise/decay time of 0.64/0.95 ms at 405 nm. Moreover, the pyroelectric responses of these ZSP heterojunction PDs are further improved by increasing the light illumination frequency. These results demonstrate that the rational construction of novel heterojunctions and utilization of the pyroelectric effect holds great potential for fabricating high‐performance self‐powered PDs.